Ration design of porous Mn-doped Na3V2(PO4)3 cathode for high rate and super stable sodium-ion batteries. (1st February 2019) - Fang, Junqi; Wang, Suqing; Yao, Xiang; Hu, Xinchao; Wang, Ying; Wang, Haihui
Abstract: A simple freeze-drying-assisted method is used to prepare various porous Mn-doped Na3 V2 (PO4 )3 /C composites. Rietveld refinement and atomic absorption spectroscopy (AAS) are applied to probe the real substitute site of Mn and demonstrate that Mn ions successfully occupy the V sites. The Mn 2+ /Mn 3+ doping in the vanadium site of Na3 V2 (PO4 )3 causes the lattice volume to expand with enlarged Na ion diffusion channels, which benefits Na + transportation and increases the ionic conductivity of Na3 V2 (PO4 )3 . Furthermore, due to the charge compensation, the presence of Mn 2+ in Na3 V2 (PO4 )3 leads to the formation of V 4+, which improves the intrinsic conductivity and stabilizes the NASICON framework. Through the XPS results of the electrode under the fully charged or discharged states, the small and reversible plateau at ca. 3.85 V of the Mn-doped Na3 V2 (PO4 )3 electrode is ascribed to the activation of the Mn 2+ /Mn 3+ redox couple. An optimized performance is achieved for Na3 V1.8 Mn0.2 (PO4 )3 /C, which exhibits a capacity of 106.8 mAh g −1 at 1 C and 77.8 mAh g −1 at up to 30 C. Even more impressive, a high capacity retention of 82% was achieved at 30 C after 10000 cycles.